Pembuatan sumur resapan dalam mengolah air limbah rumah tangga secara komunal di Desa Sumber Jaya Kecamatan Timang Gajah Kabupaten Bener Meriah Tahun 2024 - Zulfikar, Zulfikar; Aditama, Wiwit; Khairunnisa, Khairunnisa; Arianto, Budi; Sofia, Sofia; Darmiati, Darmiati; Faisal, Faisal (Jurnal PADE: Pengabdian & Edukasi, 2024)
Wastewater is defined as wastewater that has been utilized by people for a variety of purposes, including the use of clean water from homes, workplaces, stores, public spaces, industries, and other sources. In addition to the issue of clean water provision—which is crucial to investigate since clean water is a basic necessity that the community needs constantly—one of the major issues facing residential areas, particularly in urban areas, is environmental pollution brought on by improper wastewater disposal. This community service project aims to conduct actions to enhance the physical quality of the river water that flows to nearby residences by means of the planning of a simple filter. The residence of a local in the sungai area that discards rubbish into the river during the activity's planning, execution, and assessment phases is the service's goal. To get ready, a preliminary survey is carried out to assess field conditions and secure authorization. putting lectures and student activities into practice. As a result of the action, four houses now have a shared infiltration well, removing any obstacles that the residents may have had in directing their home's wastewater.